Interleukin-18 Amplifies Macrophage Polarization and Morphological Alteration, Leading to Excessive Angiogenesis - Kobori, Takuro; Hamasaki, Shinichi; Kitaura, Atsuhiro; Yamazaki, Yui; Nishinaka, Takashi; Niwa, Atsuko; Nakao, Shinichi; Wake, Hidenori; Mori, Shuji; Yoshino, Tadashi; Nishibori, Masahiro; Takahashi, Hideo (Frontiers in Immunology, 2018)
M2 macrophage promotes pathologic angiogenesis through a release of pro-angiogenic mediators or the direct cell-cell interaction with endothelium in the micromilieu of several chronic inflammatory diseases including rheumatoid arthritis and cancer where interleukin (IL)-18 also contributes to excessive angiogenesis. However, the detailed mechanism remains unclear. The aim of this study is to investigate the mechanism by which M2 macrophages in the micromilieu containing IL-18 induce excessive angiogenesis in the in vitro experimental model using mouse macrophage-like cell line, RAW264.7 cells, and mouse endothelial cell line, b.End5 cells. We discovered that IL-18 acts synergistically with IL-10 to amplify the production of macrophage-derived mediators like osteopontin and thrombin, yielding thrombin-cleaved form of osteopontin generation which acts through integrins α4/α9, thereby augmenting M2 polarization of macrophage with characteristics of increasing surface CD163 expression in association with morphological alteration. Furthermore, the results of visualizing temporal behavior and morphological alteration of macrophages during angiogenesis demonstrated that M2-like macrophages induced excessive angiogenesis through the direct cell-cell interaction with endothelial cells, possibly mediated by CD163.